Summary of Discussions From the 2019 OECD Conference on RNAi Based Pesticides - Mendelsohn, Michael L.; Gathmann, Achim; Kardassi, Dimitra; Sachana, Magdalini; Hopwood, Emily M.; Dietz-Pfeilstetter, Antje; Michelsen-Correa, Stephani; Fletcher, Stephen J.; Székács, András (Frontiers in Plant Science, 2020)
RNA interference (RNAi) is a biological process in which double-stranded ribonucleic acid (dsRNA) molecules inhibit protein expression. In recent years, the application of dsRNA has been used in the development of agricultural products for pest control. The 2019 OECD Conference on RNAi Based Pesticides (“the Conference”) brought together academic, industry, and government experts in various aspects of RNAi to discuss the current state of knowledge and topics to help in developing considerations for risk assessment. The Conference focused on environment, with some discussion of human health. Along with presentations on the use of dsRNA-based products in agriculture, government regulation, risk assessment, and a background on the Draft OECD Working Paper on ‘Considerations for the Environmental Risk Assessment of the Application of Sprayed or Externally Applied dsRNA-Based Pesticides’ (“OECD Working Paper”), the Conference included panel discussions from presenters at the end of each session and a larger discussion session with Conference participants on the environmental fate of dsRNA, non-target organism (NTO) risk assessment, and human health risk assessment. This paper summarizes input from presenters and Conference participants during these discussions. Key considerations from these discussions have already been incorporated into the OECD Working Paper, that once finalized and published, will facilitate regulators in evaluating externally applied dsRNA- based products for potential environmental risks.